A qualitative meta-synthesis of studies of patients' experience of exercise interventions in advanced cancer - Young, Julie; Lloyd, Anna; Haraldsdottir, Erna (Frontiers in Rehabilitation Sciences, 2024)
Background People with advanced cancer often experience reduced functional capacity and quality of life. Research evaluating the potential benefit of exercise programmes for limiting such decline is accumulating. However, an appraisal of the evidence that considers the patient experience of exercise programmes, what mattered to them and what motivated and encouraged them to engage in exercise, has not been published. The aim of this meta-synthesis was to identify, appraise and bring together evidence from qualitative research in this area. Methods Four databases were searched from 2nd January to 8th January 2023 for relevant studies. Qualitative studies investigating the experience of exercise as an intervention for adults with advanced cancer were included. Major findings and study characteristics were extracted. Findings were summarised, compared, and synthesised using meta-synthesis. Results Eight studies were eligible and generated seven sub themes which informed the construction of three key themes: (1) Impact of Delivery Method; (2) Emerging Motivation; and (3) Physical Impact. Conclusion The analysis revealed that exercise has the potential to positively influence all four dimensions of well-being: physical, psychological, social, and spiritual, for people with advanced cancer. Future research is required to consider the differential impact that the type, volume, and duration of exercise may have on the exercise experience for this patient group.